Understanding alignment between design approaches and student priorities for online learning platforms - Jian, Xue Jun (Department of Computer Science, 2022)
With the increasing number of public institutions turning to online learning, there is a need to understand the process of online learning development and how it aligns with student priorities for online learning platforms. This is exacerbated by the onset of COVID-19, with many institutions hastening to move their courses online during the global lockdowns, making it even more a priority to understand online learning practice. Various studies have reported on best online learning practices but deviations from student priorities still exist in reality. In practice, courses are predominantly designed from the lecturer's perspective, and student perspectives are only incorporated through feedback from course evaluations. Students are rarely given a role in the design process and are therefore unable to sculpt out their design needs for online courses. One design approach which gives a design role to students is co-design. Codesign takes into account the perspectives of all stakeholders by allowing each stakeholder to equally participate in the design process. The participation of students in design and the degree of participation they take has rarely been articulated. How does the design approach from the lecturer's perspective, where students take no part in the design process, compare to the co-design approach, where maximum participation can be achieved? How do these design approaches contribute to the deviations from student priorities? The aim of this study was to understand the alignment between design approaches and student priorities for online learning platforms and how deviations transpire. This research posited that a co-design approach, including the students as designers, might assist in alleviating these deviations. In the first part of the study, the researcher interviewed current students in an online course to understand their priorities for design. Results from the interviews were analysed and shared with students and lecturers, who were invited to prototype designs for a lesson module based on this feedback, first individually, then as a group. Another set of students were then invited to compare and evaluate the implemented prototypes in the final part of the study. The results demonstrated that a) expressed student learning priorities generally aligned with current knowledge of online learning design, b) a gap between design and reality exists for actual online course practices, c) design deviations from student priorities emerged at the beginning stages of the design process, where individual interpretation of design needs differed, d) design discussions and idea sharing during co-design alleviated these deviations, and e) co-design activities stunted the creativity of the team. Although co-design managed to bridge part of the gap between online learning platform design and student priorities, there are many factors that limit effective multistakeholder co-design. Depending on characteristics of individuals, team dynamics and design environment and conditions, the full benefits of co-design may not always be realized. Future works should explore ways of gaining mainstream adoption of design approaches such as co-design, to bridge the gap between design and reality in the online learning space.